FORMATION OF TEACHER'S READINESS FOR MASTERING AND USE OF ELECTRONIC TEACHING MANUALS - Цзэн, Цзянь; Кравченя, Эдуард (SWorldJournal, 2022)
The paper considers the possibilities of integrating a new generation of information technologies into education. It is shown that modern education in the context of the existence of big data urgently needs not only to reform the educational concept, but